Rancangan Pembelajaran dan Teknologi Dalam Militer - Susilaningsih (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Teaching design in the military field shows an increasing trend and has a broad impact. The increase in military training models is due to several factors including the application of learning and technology in military training. Training design models are a vital and long-term investment to help military personnel acquire the necessary skills and knowledge.